2007
DOI: 10.1007/s11095-007-9318-0
|View full text |Cite
|
Sign up to set email alerts
|

A Protective Allergy Vaccine Based on CpG- and Protamine-Containing PLGA Microparticles

Abstract: This study shows that allergen-specific immunotherapy with a PLGA-based allergen-delivery system in combination with CpG enhanced the induction of protective IgG2a immune responses. This may improve SIT compliance and shorten its duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 44 publications
(31 reference statements)
1
31
0
Order By: Relevance
“…An alternative co-delivery method is to administer CpG and Der p2 in biodegradable poly(lactic-co-glycolic acid) (PLGA) polymer particles. In addition to co-delivering multiple molecules, many studies have recognized the significance of PLGA particulate vaccines in stimulating robust Th1-type responses as characterized by secretion of IgG2a antibodies (29,30). Vaccination of mice with antigen-loaded PLGA microparticles and CpG, either co-loaded with antigen or injected as a solution, showed enhanced secretion of IgG2a antibodies with a greater ratio of IgG2a:IgG1 antibodies when compared to mice vaccinated with a mixture of antigen and aluminum hydroxide (31).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative co-delivery method is to administer CpG and Der p2 in biodegradable poly(lactic-co-glycolic acid) (PLGA) polymer particles. In addition to co-delivering multiple molecules, many studies have recognized the significance of PLGA particulate vaccines in stimulating robust Th1-type responses as characterized by secretion of IgG2a antibodies (29,30). Vaccination of mice with antigen-loaded PLGA microparticles and CpG, either co-loaded with antigen or injected as a solution, showed enhanced secretion of IgG2a antibodies with a greater ratio of IgG2a:IgG1 antibodies when compared to mice vaccinated with a mixture of antigen and aluminum hydroxide (31).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to co-delivering multiple molecules, many studies have recognized the significance of PLGA particulate vaccines in stimulating robust Th1-type responses as characterized by secretion of IgG2a antibodies (29,30). Vaccination of mice with antigen-loaded PLGA microparticles and CpG, either co-loaded with antigen or injected as a solution, showed enhanced secretion of IgG2a antibodies with a greater ratio of IgG2a:IgG1 antibodies when compared to mice vaccinated with a mixture of antigen and aluminum hydroxide (31). We have previously reported that PLGA particles encapsulating antigen and CpG can stimulate robust immune responses compared to vaccination of antigen and CpG in solution (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a high interest in improving current methods of SIT. Numerous studies have investigated new strategies to optimise the allergen molecules [3,4,5], the adjuvants used [6,7,8], the dosage form [9,10,11], as well as the route of allergen administration [12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…The effect of the CpG nucleotide was further strengthened when protamine was co-encapsulated for the complexation of CpG. 76 Chitosan has been used for its mucoadhesiveness that makes this particle attractive for mucosal immunity. 43 Following this line of evidence, Liu et al tested the immunotherapeutic efficiency of the IN administration of Dermatophagoides farinae extract (Der f) entrapped in chitosan microparticles.…”
Section: Arthropoda Allergensmentioning
confidence: 99%